The Role of Language, Culture and Communication in Development - Simiyu, Everlyn E.; Mbwanga, Florence M. (Machakos University, 2018)
The paper discusses the idea that culture starts at personal level and becomes a national culture and the idea that a new culture can develop from the mixing of people from different backgrounds.It explores the idea that even two people who were born and brought up together can belong to different cultures due to their different stations in life. The paper shows that the siblings who have travelled elsewhere tend to develop a different and positive culture from those who never leave home.It is about the people at the grassroots who make majority of the Kenyan population, and who make this nation and can also break it in a few hours or days. The data was collected from face to face interviews and observing people from two groups of ten respondents each in Ruiru and Ting’ang’a in Kiambu County and some of their siblings who leave away from Kiambu.The study used a control group of four siblings ( who live away from Kiambu and travel to other parts of Kenya and abroad) of four of the respondents. Both random and purposive sampling were used to get the respondents.The discussion concludes that culture, just like its medium, language, can be dynamic and that culture starts at personal level and then permeates to groups of people and the community. The paper also concludes that whatever development we achieve as Kenyans can be lost in a few days if we lack a culture of appreciating each other as Kenyans and communicating the same.That a negative culture can be detrimental to the development of a nation and actually cause its downfall. Key words: communication, culture, development, language, inclusiveness.
Keywords: Communication